The critical role of trust in experiencing and coping with energy poverty: Evidence from across Europe - Grossmann, Katrin (2021)
Trust is a fundamental ingredient of prosperous democracies. In Europe, trust in existing elected democratic institutions is fading while authoritarian nationalist movements grow. Experiences of neglect, ignorance, and inferiority are one explanation for this. This paper explores the link between the experiences of households in a state of energy poverty and their trust in institutions and social networks. Using qualitative data from ten different European countries, we show that a lack of trust in both public and private institutions is widespread among energy-poor households. Our interviewees show distrust in various dimensions. In their contacts with institutions, they report experiences of powerlessness, bad and unfair treatment, and feelings of inferiority. While some interviewees do trust single individuals within institutions, others trust only their own social networks and some have no trust in anyone. We further show how trust in networks or (people in) institutions can strengthen the coping capacities of energy-poor households while a lack of trust even cuts people off from the support they could attain and thus deepens their state of energy poverty.